2019
DOI: 10.1038/s41586-019-1416-8
|View full text |Cite
|
Sign up to set email alerts
|

Do not discard Staphylococcus aureus WTA as a vaccine antigen

Abstract: License: Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 13 publications
0
67
0
Order By: Relevance
“…Gerlach et al concluded that this novel WTA epitope was essential for the ability of S. aureus to evade host immune defenses due to its poor immunogenicity and antibody recognition (Gerlach et al, 2018). On the contrary, Dalen et al considered TarP-WTA as a highly dominant S. aureus antigen (van Dalen et al, 2019). We found that tarP also existed in other clones besides CC5 and CC398, suggesting that the tarP gene might have a broader coverage among S. aureus.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Gerlach et al concluded that this novel WTA epitope was essential for the ability of S. aureus to evade host immune defenses due to its poor immunogenicity and antibody recognition (Gerlach et al, 2018). On the contrary, Dalen et al considered TarP-WTA as a highly dominant S. aureus antigen (van Dalen et al, 2019). We found that tarP also existed in other clones besides CC5 and CC398, suggesting that the tarP gene might have a broader coverage among S. aureus.…”
Section: Discussionmentioning
confidence: 61%
“…Of note, glycosylated WTA acts as bacteriophage receptors to mediate interspecies and intergeneric HGT and takes a great part in the pathogen-host immune response. Therefore, WTA has become an attractive drug target to the infection control of S. aureus and other Gram-positive pathogens in recent decades (Winstel et al, 2015;Mistretta et al, 2019;van Dalen et al, 2019). Gerlach et al demonstrated that tarP played a crucial role in the fitness of these lineages and raised concerns of further dissemination by horizontal gene transfer, but the role of this novel RboP-β-1,3-GlcNAc WTA epitope in immune response remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our data with IgG1 antibodies against WTA suggest that naturally induced antibodies against S. aureus indeed require Fc-Fc contacts to induce complement activation on the surface of bacteria. Although we used monoclonal antibodies, it is well-recognized that IgG1 antibodies against WTA are produced during an S. aureus infection in vivo (Jung et al, 2012;Lee et al, 2015;Kurokawa et al, 2016;van Dalen et al, 2019). Also, given that excessive activation of complement has been associated with clinical manifestation of several autoimmune diseases, SpA could be used to study whether autoreactive antibodies induce IgG clustering on altered host cells.…”
Section: Discussionmentioning
confidence: 99%
“…2a ) the use of phosphoramidite building blocks would be more effective for the formation of the phosphodiester linkages 37 , 38 . In line with contemporary DNA chemistry and building on our recent experience in the generation of synthetic oligo(glycerolphosphate) and oligo(ribitolphosphate) teichoic acid antigens, we opted for the use of the dimethoxytrityl (DMTr) ether to temporarily mask the primary alcohol functions to be elongated 39 42 . Each elongation cycle is based on the iteration of a three-step sequence, comprising the coupling of the phosphoramidite with the growing chain alcohol, oxidation of the intermediate phosphite to the corresponding phosphotriester and unmasking of the primary hydroxyl on the (n + 1) oligomer.…”
Section: Resultsmentioning
confidence: 99%